Beyond the performativity of language: The linguistic turn and social constructivism in Leviathan and Air-Pump - Martini, María de los Ángeles (História da Historiografia: International Journal of Theory and History of Historiography, 2025)
Forty years after the publication of Steven Shapin and Simon Schaffer’s book, Leviathan and the Air-Pump, this paper aims to examine the philosophical commitments that the authors assumed when they recognized themselves as part of the social constructivist perspective of Strong Programme. This vision, deeply rooted in Wittgensteinian philosophy, addressed the analysis of scientific knowledge in defense of the primacy of practice. However, constructivism has been naively interpreted as limiting itself to the performativity of language. The review of these commitments allows me to explore the affinities between language and materiality in the framework of their work. Finally, I examine the approach that the authors made to the philosopher’s body as constitutive of the experimental form of life in seventeenth-century England. I seek to clarify where the conceptual effort and complexity of investigating scientific practices through Wittgenstein’s notions of form of life and language-game lay.